Effectiveness of mikhled knee exercise programme in pain and function among patellofemoral arthritis subjects. - Selvam, Monisha; Kotteeswaran, K.; Buvanesh, A. (Physiotherapy Practice & Research, 2025)
Background: Patellofemoral arthritis is a common condition causing knee pain and functional limitations. The Mikhled Knee Exercise Program (MKEP) is an emerging approach for managing this condition, but its efficacy needs further evaluation. Objective: To assess the comparative effectiveness of MKEP combined with ultrasound therapy and conventional physiotherapy combined with ultrasound therapy in managing patellofemoral arthritis. Methods: Thirty participants diagnosed with patellofemoral arthritis were randomly assigned to two groups: MKEP group (n = 15) and conventional therapy group (n = 15). The MKEP group received the Mikhled knee exercise program along with ultrasound therapy, while the conventional group received traditional physiotherapy exercises and ultrasound therapy. Both groups underwent a 6-week intervention. Pain levels were assessed using the Numerical Pain Rating Scale (NPRS), and functional status was evaluated using the Anterior Knee Pain Scale (AKPS) at baseline and after the intervention. Result: Both groups showed significant improvements in NPRS and AKPS scores after the intervention (p < 0.0001). However, the MKEP group exhibited substantially greater improvements in NPRS (mean post-test score: 3.93 vs. 4.87) and AKPS (mean post-test score: 76.14 vs. 65.93) compared to the conventional group (p < 0.0001). Conclusion: The findings suggest that the Mikhled Knee Exercise Program combined with ultrasound therapy is more effective than conventional physiotherapy with ultrasound in reducing pain and improving functional status among patients with patellofemoral arthritis.